Modulação da fotossíntese e assimilação do nitrogênio por condições de elevado CO2 atmosférico em plantas de soja - Feitosa, Antonio Glaydson de Sousa (2014)
High atmospheric CO2 concentrations limit the assimilation of CO2 and nitrogen in many species of C3 plants Thus the aim of this study was to identify how the high CO2 regulates photosynthesis and assimilation of nitrogen in soybean Therefore an experiment was conducted in growth chamber using soybean plants, 25 days old CO2 levels were applied environment ( 40 Pa) high (100 Pa) and transition to ambient conditions ( 100-40 Pa ) High CO2 was able to strongly affect trade gas with stomatal closure leading to sharp reductions in leaf transpiration (88%) and CO2 assimilation ( 48%) Recovering 69% of the initial value of net photosynthesis after the transition period at environmental conditions , however the internal CO2 concentration ( Ci) was increased by 17 times returning to the level of control after the transition the initial activity and the total Rubisco decreased 44 % and 34 % respectively Taking a 9% reduction in enzyme activation state but after the transition to the conditions of CO2 environment the initial activity and total recovered 74 % and 84 % respectively have the nitrate reductase showed a strong inhibition over that period compared to the ambient condition reaching a maximum reduction of 64 % after four days of exposure to elevated CO2 contrary this enzyme had recovered its initial capacity at 90 % after the transition period in conclusion we can say that photosynthesis and nitrate reductase activity are practically inhibited by high atmospheric CO2 mainly controlled by stomatal and metabolic limitations